AI Training and Growth Mindset Strengthen PKBM Tutors Pedagogical Readiness: Pelatihan AI dan Growth Mindset Meningkatkan Kesiapan Pedagogis Tutor PKBM - Al jamin, M Wagio; Zailani , Rinawati (Pedagogia : Jurnal Pendidikan, 2026)
General Background: The integration of Artificial Intelligence (AI) in education requires teachers’ digital competence and psychological readiness, particularly in nonformal institutions. Specific Background: Tutors at PKBM Al Mustajab initially exhibited low confidence and resistance toward AI-based learning media. Knowledge Gap: Prior studies largely focused on technical AI training in formal education, with limited integration of growth mindset interventions in PKBM contexts. Aims: This qualitative descriptive study aims to describe AI-based learning media training combined with a growth mindset approach and its pedagogical outcomes. Data were collected from 10 tutors and 1 manager through observation, interviews, and documentation, and analyzed interactively. Results: The training increased tutor confidence, active participation, independent exploration of AI tools, and the production of more interactive and contextual learning media, alongside a shift from fear to exploratory attitudes. Novelty: The study presents a systematic integration of AI technical instruction and growth mindset–based psychological intervention in nonformal education. Implications: Sustainable mentoring and institutional support are required to maintain digital transformation in PKBM settings. Highlights:• Tutors demonstrated greater autonomy in operating AI applications during training sessions.• Reflective dialogue fostered adaptive attitudes toward digital innovation.• Learning products became more contextual and visually engaging for diverse learners. Keywords: Artificial Intelligence; Growth Mindset; Learning Media Development; Nonformal Education; Teacher Professional Development